Focusing on Referral Rather than Selection for Advanced Heart Failure Therapies - Tonje Thorvaldsen (Radcliffe Medical Media, 2019)
Despite advances in heart failure treatment, advanced heart failure affects 5–10% of people with the condition and is associated with poor prognosis. Selection for heart transplantation and left ventricular assist device implantation is a rigorous and validated process performed by specialised heart failure teams. This entails comprehensive assessment of complex diagnostic tests and risk scores, and selecting patients with the optimal benefit-risk profile. In contrast, referral for advanced heart failure evaluation is an arbitrary and poorly studied process, performed by generalists, and patients are often referred too late or not at all. The study elaborates on the differences between selection and referral and proposes some simple strategies for optimising timely referral for advanced heart failure evaluation.